APPLICATION OF LAW DETERMINE THE AL-QUR'AN READING USING MICROSOFT VISUAL BASIC 6.0 - Maryani Maryani; Cut Asiana Germawaty, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Knowing the  law read the Koran is very important in reading the Koran;'s. And to be able to read well we need a persistence that in accordance with makhrajnya pronunciation, so it created a legal method of reading the Koran to use Visual Basic applications.